The Role of High-Income Households and Tourism in Advancing Energy Affordability and Financial Inclusion for Small Islands - I Wayan Koko Suryawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Energy affordability and financial inclusion remain critical challenges for small island communities, where reliance on imported fossil fuels and high energy costs disproportionately impact low-income households. At the same time, high-income households and the growing tourism sector on these islands hold significant financial capacity to drive equitable energy transitions. This perspective explores the role of high-income stakeholders and tourism operators in promoting energy affordability through retribution mechanisms, adaptive service assets, and flexible organizational models. By leveraging financial resources and investing in clean energy solutions, high-income households and tourism businesses can contribute to a sustainable energy future that benefits all members of the community, bridging the gap between economic growth, energy equity, and environmental sustainability.